Breath-Holding Spells - J Gordon Millichap (Pediatric Neurology Briefs, 1996)
The clinical characteristics, types, diagnosis, and management of breath-holding spells are reviewed from The Department of Pediatrics (Neurology), Park Nicollet Medical Center, Minneapolis, MN.